The impacts of Resource Development Projects on Community Livelihoods in Papua New Guinea: A Case Study From Mining and Agriculture Projects - Essacu, Francis Essacu (European Journal of Sustainable Development, 2018)
The impacts of natural resource development projects have documented positive impacts on local communities, but there is much less evidence of long-term community impacts or benefits as development outcomes. Understanding these impacts of resource development projects on communities’ livelihoods, stability and prosperity is fundamental to the achievement of sustainable development outcomes in rural communities in Papua New Guinea (PNG), as it plays an important role in the livelihoods of rural population. To explore the relationship between natural resource-based development projects and community livelihoods capacity as sustainable development outcomes, an interview data from 90 participants in two provinces of PNG associated with resource projects were collected and analyzed. Community livelihoods impacts were assessed using Likert Scale and thematic network analysis to determine impacts on development outcomes on stability and prosperity in the community. The findings demonstrated that the scale and levels of impacts on communities in terms of livelihoods assets-bases, stability and prosperity; were reflective and indicative of the form and nature of development projects in the region, and the difference in development stages of natural resource projects in each of the regions. Keywords: Natural resources projects, mining, agriculture, community livelihoods, sustainable development outcomes, stability, prosperity.